Total gadolinium tissue deposition and skin structural findings following the administration of structurally different gadolinium chelates in healthy and ovariectomized female rats - Wáng, Yì-Xiáng J. (Quant Imaging Med Surg, 2015)
OBJECTIVE: To assess the retention of gadolinium (Gd) in skin, liver, and bone following gadodiamide or gadoteric acid administration. METHODS: Gd was measured in skin, liver and femur bone in female rats 10 weeks after administration of 17.5 mmol Gd/kg over 5 days of Gd agents. Rat skin microscopy, energy filtering transmission electron microscopy and elemental analysis were performed, and repeated after receiving the same dosage of gadodiamide in rats with osteoporosis induced with bilateral ovariectomy (OVX). The OVX was performed 60 days after the last injection of gadodiamide and animals sacrificed 3 weeks later. RESULTS: Gd concentration was 180-fold higher in the skin, 25-fold higher in the femur, and 30-fold higher in the liver in rats received gadodiamide than rats received gadoteric acid. The retention of Gd in the skin with gadodiamide was associated with an increase in dermal cellularity, and Gd encrustation of collagen fibers and deposition inside the fibroblasts and other cells. No differences in Gd concentration in liver, skin, and femur were observed between rats receiving gadodiamide with or without OVX. CONCLUSIONS: Gd tissue retention with gadodiamide was higher than gadoteric acid. Tissues Gd deposition did not alter following gadodiamide administration to ovariectomized rats.